Synthesis and characterization of a nanofilter with carbon nanotubes for the removal of water contaminants - Nora, Robson Dalla; Dorfey, Daiene; Mortari, Sergio Roberto; Machado, Fernando Machado; Volkmer, Tiago Moreno; Swarowsky, Alexandre (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
The interest in nanotechnology as a mitigation tool of environmental problems, specifically the nanofiltration, is noticeable for the treatment of drinking water and wastewater. The aim of this work was to prepare and characterize Multiple Walls Nanotubes Nanofilters (MWNT), composed by polyethylene glycol (PEG), chitosan and sodium sodium sulfate (SDS) to remove contaminants in water. Different proportions of PEG 6000 K, chitosan and MWNT/SDS solution were studied to obtain the desired permeability. The nanofilter was characterized by scanning electron microscopy, Raman spectroscopy; its pore size and porosity was determined by the nitrogen adsorption method. The results showed that the produced nanofilter has a pore size average 384 nm to 493 nm and lower permeability.